Availability of Sports Open Spaces in Tawangharjo District, Grobogan Regency: A Sport Development Index Perspective - Pratama, Rivan Saghita; Seftiana, Seftiana; Wahadi, Wahadi; Aji, Tri; Nadzalan, Ali MD; Imron, Fatkhul; Santosa, Teguh; Kusumawardhana, Buyung; Setia Lengkana, Anggi (Journal of Sport Science and Education, 2024)
The number of open spaces and the population aged seven years and above are known to determine the ratio of open spaces to the Sports Development Index. This study used a survey method with a quantitative descriptive approach, using sports open spaces as research variables. The sampling technique was based on the Sports Development Index (SDI), namely the Multistage Random Sampling. The population of this study was residents of Tawangharjo Village, Tarub Village, and Godan Village. The availability of open sports spaces in the Tawangharjo sub-district, represented by 3 villages, namely Tawangharjo, Tarub, and Godan, is in a low category. The solution is to improve sports development in the open space aspect, namely by involving the government to improve the welfare of the people, such as by providing the most superior sports facilities in the region, including football, volleyball, martial arts, and jogging tracks. The role of the community can help develop sports development, such as cooperation in cleaning abandoned sports open spaces.